Assessment of the application for renewal of authorisation of Bactocell® (Pediococcus acidilactici CNCM I‐4622) as a feed additive for weaned piglets, pigs for fattening, minor porcine species (weaned and for fattening), chickens for fattening, laying hens and minor avian species for fattening and for laying and its extension of use to all growing pigs and all avian species. (15th May 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on Bactocell ® ( Pediococcus acidilactici CNCM I‐4622) in the context of the renewal of the authorisation for weaned piglets, pigs for fattening, minor porcine species (weaned and for fattening), chickens for fattening, laying hens and minor avian species for fattening and for laying when used as a zootechnical feed additive (gut flora stabiliser) in feed or in water for drinking. In addition, the applicant requested the extension of use for suckling piglets, minor pig species (growing/for fattening), chickens reared for laying, chickens reared for breeding purposes, chickens for breeding purposes, turkeys and minor avian species (including non‐food producing/ornamental birds) reared for laying/breeding purposes and for breeding purposes when used as in feed or in water for drinking. The applicant has provided evidence that the additive currently on the market complies with the conditions of authorisation. The additive is safe for the target species, consumers and the environment as well. The additive is non‐irritant to skin and eyes and is not a dermal sensitiser but should be considered a respiratory sensitiser. Considering the high dusting potential of the formulations, exposure of users by inhalation is very likely. The additive, at the level of 1 × 10 9 CFU/kg feed (5 × 10 8 when delivered in water), has the potential to be efficacious in the new species proposed: chickens reared for laying, chickens reared for breeding purposes, chickens for breeding purposes, turkeys and minor avian species reared for laying/breeding purposes and for breeding purposes (including non‐food producing/ornamental birds) and in suckling piglets and minor porcine species (growing/for fattening).